2013
DOI: 10.1007/s10549-013-2691-y
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of preoperative docetaxel with or without capecitabine after 4 cycles of 5-fluorouracil–epirubicin–cyclophosphamide (FEC) in early-stage breast cancer: exploratory analyses identify Ki67 as a predictive biomarker for response to neoadjuvant chemotherapy

Abstract: This randomized, multicenter study compared the efficacy of docetaxel with or without capecitabine following fluorouracil/epirubicin/cyclophosphamide (FEC) therapy in operable breast cancer and investigated the role of Ki67 as a predictive biomarker. Patients were randomized to 4 cycles of docetaxel/capecitabine (docetaxel: 75 mg/m2 on day 1; capecitabine: 1,650 mg/m2 on days 1–14 every 3 weeks) or docetaxel alone (75 mg/m2 on day 1 every 3 weeks) after completion of 4 cycles of FEC (5-fluorouracil 500 mg/m2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 25 publications
7
36
0
Order By: Relevance
“…The nuclear protein Ki67 is often used as a marker of cellular proliferation, and is a good predictive and prognostic marker widely used in clinical practice of breast cancer [1][2][3][4][5][6][7]. Studies have demonstrated that Ki67 assessment helped to more reliably define prognosis in patients with ER-positive and HER2-negative breast cancers [2,4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nuclear protein Ki67 is often used as a marker of cellular proliferation, and is a good predictive and prognostic marker widely used in clinical practice of breast cancer [1][2][3][4][5][6][7]. Studies have demonstrated that Ki67 assessment helped to more reliably define prognosis in patients with ER-positive and HER2-negative breast cancers [2,4].…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear proliferation marker Ki67 is used as a predictive marker for response to chemotherapy and is associated with patient prognosis in breast cancer [1][2][3][4][5][6][7]. Assessment of Ki67 labeling index (LI) by immunohistochemical staining has been widely used in pathological evaluation of breast cancer clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies have examined dose-dense therapy and the combination of agents, such as capecitabine, gemcitabine, carboplatin, and bevacizumab, with the standard preoperative chemotherapy with anthracyclines and taxanes. [7][8][9][10][11][12][13] Although these regimens generally tend to increase the pCR rate, they also increase the incidence of serious adverse events and there have been no reports indicating that they improve long-term prognosis; therefore, no new treatment regimens showing better efficacy and safety than the existing standard treatments have been established.…”
Section: Discussionmentioning
confidence: 99%
“…These include dose-dense therapy and chemotherapy with agents that do not show crosstolerance, including capecitabine, gemcitabine, carboplatin, and bevacizumab. [7][8][9][10][11][12][13] Abraxane (nab-paclitaxel) is a human albumin-bound formulation of paclitaxel nanoparticles of 130 nm in size. It is a novel taxane formulation developed to avoid side effects, such as neuropathy and allergic reactions, caused by Cremophor/ethanol found in conventional Cremophorepaclitaxel formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development of treatments targeting osteopontin-c may be beneficial for the treatment of breast cancer. (21) examined the role of Ki-67 as a predictive biomarker of treatment response in a randomized, multicenter study to compare the effectiveness of docetaxel subsequent to treatment with fluorouracil/epirubicin/cyclophosphamide with or without capecitabine, in patients with operable breast cancer. The endpoint was the rate of pathological complete response (pCR).…”
Section: Literature Searchmentioning
confidence: 99%